Pemanfaatan Jamur Grigit Dalam Pembuatan Bakso Ikan Lele Dumbo - Irene Cahya Maharani; Vonny Setiaries Johan; Rahmayuni Rahmayuni (Agricultural Faculty, 2022)
The purpose of this research to obtain the best ratio of dumbo catfish and split gill mushrooms in making meatballs. This research used a completely randomized design with four treatments and four replications, which followed Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research was the ratio of dumbo catfish and split gill mushrooms, i.e. 90:10, 80:20, 70:30, and 60:40. The result showed that the ratio of dumbo catfish and split gill mushrooms had significantly affected moisture, ash, protein, fat, crude fiber, total plate number, as well as sensory characteristic of color, flavor, taste, and texture. Based on the result of this research the chosen treatment is 90:10 which have 64.65% moisture content, 1.21% ash content, 10.63% protein content, 0.92% fat content, 0.36% crude fiber content, 6,5 x 104 total plate number content and is preferred hedonically with a description of grayish white color, smelled of mushroom, mushroom and fish taste, and chewy texture.